Structural basis for gating the high-conductance Ca2+-activated K+ channel - Hite, Richard K.; Tao, Xiao; MacKinnon, Roderick (Nature (London), 2017)
The precise control of an ion channel gate by environmental stimuli is crucial for the fulfilment of its biological role. The gate in Slo1 K + channels is regulated by two separate stimuli, intracellular Ca 2+ concentration and membrane voltage. Slo1 is thus central to understanding the relationship between intracellular Ca 2+ and membrane excitability. Here we present the Slo1 structure from Aplysia californica in the absence of Ca 2+ and compare it with the Ca 2+ -bound channel. We show that Ca 2+ binding at two unique binding sites per subunit stabilizes an expanded conformation of the Ca 2+ sensor gating ring. These conformational changes are propagated from the gating ring to the pore through covalent linkers and through protein interfaces formed between the gating ring and the voltage sensors. The gating ring and the voltage sensors are directly connected through these interfaces, which allow membrane voltage to regulate gating of the pore by influencing the Ca 2+ sensors. Two complementary studies present the full-length high-resolution structure of a Slo1 channel in the presence or absence of Ca 2+ ions, in which an unconventional allosteric voltage-sensing mechanism regulates the Ca 2+ sensor in addition to the voltage sensor’s direct action on the pore. Slo1 potassium channel structure and activity Dual activation by voltage and calcium ions makes Slo1/BK channels essential to processes that couple membrane electrical excitability and cellular calcium signalling, such as muscle contraction or neuronal communication. In two complementary studies, Roderick MacKinnon and colleagues present full-length structures for a Slo1 channel, either in the presence or the absence of Ca 2+ ions, suggesting an unconventional allosteric mechanism, whereby the voltage sensor regulates the Ca 2+ sensor instead of the channel's pore directly. These findings explain a large body of biochemical, genetic and physiological data, from both basic and clinical research.